Estudo das propriedades Mesomórficas e Fotofísicas de 4- Alcoxibenzoatos de 4- (Quinoxalin-2-Il)Fenila e derivados de Alcóxi-(E)-3-Estirilquinoxalin-2(1h)-ONA - Costa, Erivaldo Paulino da (2023)
The development of functional organic materials has proved relevant to many fields. Liquid crystals are very relevant to optical electronics industry, as well as fluorescent compounds, which are commonly relevant in the development of sensors. The present thesis is divided into two main parts: the first one is centered in the study of liquid crystal properties of 4-(quinoxalin-2-yl)phenyl 4- alkoxybenzoates (QX1, QX2, DMQX1 e DMQX2). These target-compounds were obtained in good yields from four-step protocols and properly characterized by spectroscopic techniques. All quinoxaline derivatives were verified to present liquid crystalline behavior with mesophases ranging up to 112 oC, which were identified as both nematic and smectic mesophase, except compound DMQX1, which was a nematic liquid crystal. IN general, structural features do not affect considerably the mesomorphic behavior of these compounds, which were properly characterized by polarized optical microscopy based on classical Schieleren (nematic) and fan-shaped (smectic) patterns, among non-conventional textures. Exact phase transition temperatures were verified by differential scanning calorimetry. In the second part of this thesis, photophysical properties of alkoxy-(E)-styrylquinoxalin-2(1H)-one derivatives (SQX1-SQX3) were investigated by UV-Vis and fluorescence spectroscopies in different organic solvents (methanol, acetonitrile, dichloromethane and hexane) and in aqueous medium. The presence of a second alkoxy substituent as well as solvent effect do not affect considerably absorptions in the visible region, with ranging of the maximum wavelength up to 10 nm (398–408 nm). On the other hand, these two factors have great impact in the emissive properties, verified by Stokes shift up to 88 nm and 137 nm for SQX1 and SQX2, respectively, in methanol. In general, methanolic solutions presented emissions in higher wavelength, whereas more intense emissions were verified in dichloromethane. Fluorescence spectra in hexane showed two emission band in the visible region, which may be associated to hydrogen-bonding dimerization of the SQX derivatives, especially due to their relative intensities varying depending on the concentration of the dyes in solution. Reversible cis-trans isomerization was observed by UV-Vis spectroscopy in all solvents under incidence of light (365 nm or 254 nm), what is expected from literature data, however, a distinct behavior was verified for disubstituted SQX due to a new band at 283 nm, which may be associated to a photochemical [2+2] process. Lastly, addition of water to methanol and acetonitrile solutions of SQX induces to increasing in emission due to aggregation. Structural aspects are currently been discussed based on new experiments and theoretical calculations in development, in attempt to justify the photophysical properties of these SQX derivatives.